Approximation for the conditional distribution of the MLE with application to autoregression - Marsh, Patrick (Pushpa Publishing House, 2014)
The famous p* formula provides a higher-order approximation for the conditional distribution of the maximum likelihood estimator given an exact ancillary. By collating well known existing results including application of a formal higher-order expansion the formula is generalized for the case of approximate ancillaries. Applied to the class of autoregressive models a case for conditional inference is made and the accuracy of the resulting approximation is demonstrated numerically.